Effectiveness of Biofeedback Therapy in Patients with Bowel Dysfunction Following Rectal Cancer Surgery: A Systemic Review with Meta-Analysis - Li H; Guo C; Gao J; Yao H (Dove Medical Press, 2022)
Haoze Li, Ce Guo, Jiale Gao, Hongwei Yao Department of General Surgery, Beijing Friendship Hospital, Capital Medical University, Beijing Key Laboratory of Cancer Invasion and Metastasis Research and National Clinical Research Center for Digestive Diseases, Beijing, 100050, People's Republic of ChinaCorrespondence: Hongwei YaoDepartment of General Surgery, Beijing Friendship Hospital, Capital Medical University, Beijing Key Laboratory of Cancer Invasion and Metastasis Research and National Clinical Research Center for Digestive Diseases, 95 Yong-an Road, Xi-Cheng District, Beijing, 100050, People's Republic of China, Email yaohongwei@ccmu.edu.cnObjective: To identify, systematically review and synthesize the evidence on the effectiveness of biofeedback therapy in patients with bowel dysfunction following rectal cancer surgery.Data Sources: Four electronic databases (PubMed 1974- 2021; Embase1980- 2021; Cochrane databases and the trial registers) were systematically searched by reviewers from inception through March 2021.Study Selection: Randomized controlled trials (RCTs), cohort studies, and case series studies were included for adults with bowel dysfunction following rectal cancer surgery. All participants received an intervention of biofeedback treatment. Any outcomes that can evaluate the patient's bowel function were the primary research endpoint, while the quality of life was the second endpoint. The disagreements between the two reviewers were resolved after discussion and the third independent reviewer's ruling. As a result, 12 of 185 studies met selection criteria and were included in the review.Data Extraction: We designed an electronic data extraction form and data were extracted independently. The methodological quality of included studies was assessed using the Cochrane Risk of Bias, the MINORS scale, and the Institute of Health Economics scale.Data Synthesis: Meta-analyses were conducted for case series only and narrative syntheses were completed. Key findings included significant improvements in bowel function as well as health-related quality of life after biofeedback therapy. (Wexner score: t=7, MD=3.33; 95% CI [2.48, 4.18]) and (Vaizey score: t=3, MD=2.46; 95% CI [1.98, 2.93]). Subgroup analysis of Wexner score: receiving electrical stimulation therapy (t=3, MD=2.36; 95% CI [1.51, 3.22]), not receiving electrical stimulation (t=4, MD=3.79;95% CI[2.66, 4.93]); not receiving adjuvant chemoradiotherapy (t=3, MD=2.42;95% CI[1.61, 3.24]), chemotherapy and radiotherapy (t=1, MD=4.10; 95% CI [2.90, 5.30]), radiotherapy and chemotherapy on parts of patients (t=2, MD=3.46;95% CI [1.41, 5.51]), chemotherapy (t=1, MD=4.81; 95% CI [3.38, 6.24]); performing ISR (t=2, MD=3.32;95% CI [0.37, 6.27]), performing AR (t=4, MD=3.08; 95% CI [2.12, 4.04]), performing PLRAS surgery (t=1, MD=4.10;95% CI[2.90, 5.30]).Conclusion: Although biofeedback therapy may improve intestinal function and quality of life as well as anal function reflected by ARM after surgery, patient satisfaction is still unclear. Due to the scarcity of data, good-quality research is required to delve deeper.Clinical Trial Registration Number: CRD42020192658.Keywords: biofeedback, fecal incontinence, rectal neoplasms, surgery, rehabilitation